PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI PADA INDUSTRI ALAS KAKI PT. BO KYUNG PASURUAN) - Priyanto, Wahyu Budi (Journal of Innovation in Business and Economics, 2016)
Compensation is also self motivation factor for employees, where those things end in high-low level of work result or performance. This research purposes to test the effect of transformational leadership style, compensation, and motivation of employee’s performance, motivation as an effect mediator from transformational leadership style and compensation to employee’s performance in PT. Bo Kyung Pasuruan. This research is explanatory. In this research uses 96 samples from 2719 employees that work in PT. Bo Kyung Pasuruan. The result of Partial Least Square (PLS) this research shows that transformational leadership style is positively effected but not significant to motivation and employee’s performance. Motivation affect transformational leadership style of employee’s performance, and motivation does not influence compensation of employee’s performance in PT. Bo Kyung Pasuruan.Keywords: Compensation, Employees Performance, Motivation,Transformational Leadership.